2017
DOI: 10.1093/hmg/ddx136
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of ALS/FTD-linked mutant CCNF in zebrafish leads to increased cell death in the spinal cord and an aberrant motor phenotype

Abstract: Amyotrophic lateral sclerosis (ALS) is a rapidly progressive, fatal neurodegenerative disease characterised by the death of upper and lower motor neurons. Approximately 10% of cases have a known family history of ALS and disease-linked mutations in multiple genes have been identified. ALS-linked mutations in CCNF were recently reported, however the pathogenic mechanisms associated with these mutations are yet to be established. To investigate possible disease mechanisms, we developed in vitro and in vivo model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 20 publications
1
43
0
Order By: Relevance
“…Comparable with TBK1, CCNF interacts with SQSTM1, an autophagic receptor that recognizes and transfers ubiquitinated proteins for autophagic degradation [63]. In a recent study in zebrafish, disruption of axonal outgrowth by the mutant Ser621Gly CCNF was observed, suggesting a toxic gain-offunction mechanism for CCNF mutations in ALS patients [64].…”
Section: Ccnfmentioning
confidence: 99%
“…Comparable with TBK1, CCNF interacts with SQSTM1, an autophagic receptor that recognizes and transfers ubiquitinated proteins for autophagic degradation [63]. In a recent study in zebrafish, disruption of axonal outgrowth by the mutant Ser621Gly CCNF was observed, suggesting a toxic gain-offunction mechanism for CCNF mutations in ALS patients [64].…”
Section: Ccnfmentioning
confidence: 99%
“…Temporary overexpression of human cyclin-F (CCNF) in zebrafish embryos increases the levels of cleaved caspase-3 and cell death in the spinal cord. The mutant CCNF zebrafish also developed an MN axonopathy, which consists of shortened primary MN axons and an increased frequency of aberrant axonal branching (Hogan et al, 2017).…”
Section: Aberrant Axonal Branchingmentioning
confidence: 99%
“…There is the potential for toxicity to arise when overexpression is introduced into a system and this is of importance during early development when vital systems such as the nervous system are being established. In particular, the generation of models of ALS (and likely most neurodegenerative diseases) may be fraught with difficulties as many of these genes are ubiquitously expressed during development before becoming restricted to the central nervous system [6] [13]. This suggests that the toxicity detailed here is not specific to CCNF expression during developmental stages and may be a factor in the establishment of other models.…”
Section: Limitationsmentioning
confidence: 99%
“…Additionally, mutations in CCNF have recently been reported in two clinically, pathologically and genetically linked neurodegenerative diseases-amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) [5]. To date, only one in vivo model has been established as a tool to investigate CCNF dysfunction-a zebrafish model that transiently overexpressed an ALS-FTD mutation in CCNF (CCNF S621G) [6]. This model demonstrated neurological defects associated with expression of CCNF S621G, including a motor axonopathy and impaired motor function.…”
Section: Introductionmentioning
confidence: 99%